Analysis of dissipative structure on the basis of the Gaussian variational principle - Gafiichuk , V. V.; Lubashevsky , I. O. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The Gauss variational principle is suggested as a method of finding the solutions of dissipative systems. Using as an example a system of two reaction-diffusion equations, approximate solutions are found for the case of auto-solitons and periodic dissipative structures.